Effects of 9 oral care solutions on the prevention of oral mucositis: a network meta-analysis of randomized controlled trials. Issue 16 (April 2020) - Yu, Ya-Ying; Deng, Jia-Lin; Jin, Xian-Rong; Zhang, Zhong-Zu; Zhang, Xiao-Hua; Zhou, Xin
Abstract: Background: Oral mucositis (OM) is a common, disabling, and severe early effect of chemotherapy and radiotherapy that limits the effectiveness of anticancer therapy. The prevention and treatment of OM in patients with malignant tumors is an urgent problem in the field of anticancer therapy. Methods: Databases including PubMed, Embase, Scopus, The Cochrane Library, and Google Scholar were searched to collect published randomized control trials (RCTs) about the effects of different oral care solutions on the prevention of OM from inception to January 2019. We used the Cochrane Handbook to assess the methodological quality of the RCTs. Two of the authors independently extracted the articles and predefined data. Network meta-analysis was then performed using Stata 15.0 software. Results: A total of 28 RCTs involving 1861 patients were included. The results of network meta-analysis showed that chlorhexidine, benzydamine, honey, and curcumin were more effective than placebo ( P  < .05) and that honey and curcumin were more effective than povidone-iodine ( P  < .05). Probability ranking according to the Surface Under the Cumulative Ranking curve showed the following treatments: curcumin, honey, benzydamine, chlorhexidine, allopurinol, sucralfate, granulocyte-macrophage colony-stimulating factor, povidone-iodine, and aloe. Conclusion: Our preliminary results indicate that curcumin and honey may serve as the preferred options for patients to prevent OM. The findings may offer an important theoretical basis for clinical prevention and treatment. However, this conclusion still requires an RCT with a larger sample size for further verification.